Integration of Heat Exchangers, Compressor, and Steam Reutilization for Energy Efficiency Improvement in Thermal Systems of Dimethyl Ether (DME) Production - Wijaya, Fikri; Putri, Gisela Fortunata; Sukmajati, Citra Puspita; Dewi, Anggita Martha; Asyhari, Widya Meilinda Nuri (Journal of Chemical Engineering Research Progress, 2024)
Dimethyl ether (DME) is widely recommended as an environmentally friendly aerosol and green refrigerant due to its low ozone depletion potential and lower global warming potential. Dimethyl ether is produced through the dehydration of methanol which has the potential to be an environmentally friendly alternative fuel. This research addresses the improvement of energy efficiency in dimethyl ether (DME) production through the modification of a heat transfer unit using Aspen HYSYS process simulation software. Dimethyl ether is an environmentally friendly chemical with low global warming potential, which is produced through methanol dehydration. This study focuses on the replacement of heaters and coolers. These modifications successfully improved energy efficiency by reducing net energy consumption from 4.867e+006 kJ/h to 3.268e+005 kJ/h. Despite the decrease in energy efficiency, the conversion rate remained the same at 99.7%.  This research shows that modification of the heat transfer system can support more energy-efficient and sustainable DME production.